Scientific Article Writing Mentoring for the English Subject Teacher Association in Palangka Raya - Erliana, Santi; Pratika, Dellis; Sulistiyana, Levika Egita (LP2M of Institute for Research and Community Services - UIN Walisongo, 2023)
This community service aimed to address the professional development needs of teachers to enhance their career prospects. Teachers must compile portfolios to accumulate credit points for career advancement, thus necessitating their proficiency as teacher-writers. Hence, this sustainable community service sought to assist English as a Foreign Language (EFL) teachers in secondary high schools throughout Palangka Raya in comprehending the fundamentals of scientific writing, producing scientific articles, conducting research, and drafting research reports. The Participatory Action Research (PAR) methodology, which focuses on community empowerment, was employed for this endeavor. The activities were carried out over 12 workshop sessions involving 30 EFL teachers from the English Subject Teachers Association (MGMP) for junior and senior high schools in Palangka Raya. Before and after the workshops, KWL worksheets and WhatsApp Group discussions were utilized to facilitate the teachers' learning process. The results demonstrated that: (1) mentoring activities were executed effectively, with 80% of the planned materials successfully delivered to the participants; (2) participants expressed a positive perception of the activities, including satisfaction, relevance to their needs, comprehension, and overall significance.